Negara Kesejahteraan (Welfare State) dalam Pelaksanaan Kebijakan BPJS Kesehatan di Kabupaten Tabanan (Jurnal Nawala Politika, 2022)
This study aims to see how the local government of Tabanan Regency realizes social welfare in fulfilling public health services in Tabanan Regency. By using the Welfare State theory by Esping Andersen, the welfare state is generally identified with the following characteristics, namely the services and social policies provided by the state to its citizens and the form of state responsibility in providing basic services such as health. This study used descriptive qualitative method. The findings of this study indicate that the local government of Tabanan Regency provides health service guarantees to the community by trying to increase the number of BPJS Health membership so that all its people can be covered by health insurance. The government focuses on increasing participation which has an impact on the image of a good government and loves the people. However, this has not been fully optimal in meeting the welfare of the community in health services with the existence of political interpretations that have resulted in the emergence of social jealousy within the Tabanan Regency community.